Teacher Strategies for Overcoming Students’ Difficulties in EFL Learning at MTs Al-Wasilah Lemo - Mutmainna Hasan; Maemuna Muhayyang; Muhammad Arham (Fakultas Sastra - Universitas Muslim Indonesia, 2026)
This study aims to identify students’ difficulties in learning English as a Foreign Language (EFL), examine the reasons behind teachers’ selection of teaching strategies, and explore how these strategies are implemented in the classroom. This research employed a descriptive qualitative method. The data were gathered via classroom observations and semi-structured interviews with two English teachers and eighth-grade students at MTs Al-Wasilah Lemo. The results indicated that students encountered difficulties in five areas: cognitive, affective, linguistic, social, and environmental. The predominant challenges were identified in the cognitive and affective domains. To mitigate these issues, teachers employed three primary strategies: drills and repetition, pair work and group discussion, and role play. Drills and repetition facilitated enhancements in students’ pronunciation and vocabulary retention, although they occasionally led to boredom. Pair work and group discussion promoted active engagement and peer learning, although some students remained passive. Role plays bolstered students' confidence and speaking skills by offering meaningful and engaging learning experiences. This study concludes that the integration of these strategies effectively assists students in surmounting their challenges in EFL learning. Therefore, teachers are encouraged to apply varied and student-centered strategies to create a supportive and effective learning environment.